The Confession of the Other: Mohsin Hamid’s The Reluctant Fundamentalist - Mariya Shymchyshyn (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The September 11th attacks on the U.S. caused unanticipated changes in the global arena. Their depiction in fictional discourse contributed to the broad understanding of the events and their memorialization. In this paper, I analyze Mohsin Hamid’s novel The Reluctant Fundamentalist which presents the perspective of those who were silenced in the dominant rhetoric of the 9/11 tragedy and were single-mindedly blamed as “evil others.” Through his monologue, Changez, the homodiegetic narrator of the novel, explicitly demonstrates the intention to present the voice of the Other. The narrator of the novel asks readers to listen to the other side of the conflict and not to judge all Muslims as bloodthirsty fundamentalists. Changez proposes that the American agent consider his view in order not to blame him but to understand the roots of his anger. In addition to his appeal for constructive dialogue between the West and the East, the narrator of the novel brings forward the critical revision of the U.S.’ international politics. One of the messages is that after causing so much grief and misfortune abroad, the U.S. cannot play the role of an innocent observer. I conclude that the diegesis of the novel opens new ways for productive dialogue between nations and countries.